First report on dog bite epidemiology and Rabies diagnosis in stray dogs: a one health study from Puducherry - Killada, Abhiram Naidu; Rekha, V. Bhanu; Isloor, Shrikrishna; Kumar, V. J. Ajay; Vijayalakshmi, P.; Quintoil, Nithya; Subramanian, Sundarachelvan; Singh, Shraddha; Banakar, Neha M.; Deepan, G.; Ravivarman, S. (Frontiers in Veterinary Science, 2025)
IntroductionRabies is a fatal zoonotic disease transmitted primarily through dog bites. Monitoring bite incidence and reliable rabies diagnostic methods are crucial for effective rabies control, especially in endemic regions. So, the present study was conducted to estimate the burden of dog bite cases in humans and animals, and to confirm the presence of rabies using various diagnostic tests among dogs in Puducherry, India.Materials and methodsA regional descriptive study was done with objectives to collect the data on human and animal dog bite cases from 2020 to 2023 and 25 brain samples from dogs suspected of rabies were collected post-mortem using the foramen magnum method. Samples were tested using Lateral Flow Assay (LFA), Direct Fluorescent Antibody test (DFA), Direct Rapid Immuno-histochemistry Test (dRIT), and One-step RT-PCR. Sensitivity and specificity of these tests were compared using DFA as the gold standard to estimate the burden of rabies in stray dogs.ResultsDog bite cases in humans increased from 16,652 in 2020 to 20,063 in 2023, with December consistently reporting the highest average number of bites (1787.25 cases). Animal bite cases rose from 948 in 2022 to 1,131 in 2023, affecting dogs (56.1%), goats (30.7%), cattle (14.3%), and cats (0.9%). Of the 25 dog brain samples tested, 19 (76%) were rabies positive. LFA, dRIT, and RT-PCR demonstrated 100% sensitivity and specificity compared to DFA. Rabies cases were nearly equal in females (52.6%) and males (47.4%), with 68.4% occurring in dogs under 3 years. The highest monthly cases were observed in May and October, with Reddiarpalayam and Lawspet being the most affected regions.Discussion and conclusionThe study reveals a concerning rise in dog bite cases and confirms the utility of LFA, dRIT, and RT-PCR as reliable alternatives to DFA for rabies diagnosis. Enhanced surveillance, public awareness, and vaccination programs are essential to control rabies in Puducherry.